A better understanding of CNTs chemical purification and functionalization processes - Azhari, Saman; Hamidon, Mohd Nizar; Hasan, Intan Helina; Mohd Kusaimi, Muhammad Asnawi; Mohd Chachuli, Siti Amaniah; Mohd Azhari, Nur Alin; Ismail, Ismayadi (IEEE, 2018)
Purification and functionalization of carbon nanotubes have been examined using different acid treatments. CNTs treatment may vary depending on the desired outcome. The results show that HCl as a strong acid, oxidizes all the materials present in the sample. HNO3 acts as an oxidizing agent which is useful to produce functional CNTs. H2O2 behaves as a regulator in presence of both acids. The results suggest that H2O2 may be a critical element to control the outcome of CNTs purification and functionalization process.